Análise e comparação de sete métodos numéricos utilizados na determinação dos parâmetros da curva de Weibull aplicados aos dados de velocidade do vento coletados na cidade de Paracuru-CE e Camocim-CE - Sousa, Ricardo Coelho de (2011)
This dissertation deals with the analysis and comparison of 7 (seven) numerical methods for the assessment of effectiveness in determining the parameters for the Weibull distribution, using wind speed data collected in Camocim and Paracuru cities, in the period from August 2004 to April 2006, obtained by the Department of Infrastructure of the Ceará state. Using the method of analysis of variance, RMSE test and the chi-square and analysis of power for test to compare the proposed methods, this study aims to determine which method was most effective in determining the shape parameters of Weibull distribution for the available data, aiming to establish criteria to a better utilization of wind power in the of Ceará state, which is in national prominence in the use of renewable sources for electricity generation.